Graphitized porous carbon prepared from pyrolysis of Sterculia scaphigera and its application in lithium ion batteries1. Issue 58 (25th June 2015) - Wang, W. X.; Wan, Y.; Wu, S. F.; Li, M. C.; Cao, L. J.; Lv, F. C.; Yang, M. Y.; Sun, Z. F.; Sun, R.; Lu, Z. G.
<x xml:space="preserve">Abstract</x> Sterculia scaphigera exhibits exceptional capability to inhale a large amount of water, which is accompanied by great volume expansion.